Strategi Pembinaan Wirausaha Pemula Berbasis Kampus - Alif Ilman Mansyur (Al-Azhar Journal of Islamic Economics, 2023)
Entrepreneurial ethos must always be developed, maintained, cared for and fostered, so that it is of great benefit to society. various efforts have been made to foster entrepreneurship in the campus environment. This study aims to explain the effect of entrepreneurship education on student entrepreneurship motivation in the Tadris IPS Study Program, Mataram State Islamic University. This research uses qualitative research and collects data using purposive sampling and descriptive analysis techniques. The number of samples used was 40 respondents using non-probability sampling techniques, especially purposive sampling. The results of testing the hypothesis in the initial observations indicate that there is an influence of entrepreneurship education and motivation that really needs to have a significant effect on entrepreneurial intentions. Based on the results of this study, it is better for entrepreneurs or students to pay attention to the influence of entrepreneurship education, self-efficacy and the need for achievement as a material consideration in applying entrepreneurial intentions, because these three variables significantly have a positive effect on novice entrepreneurial intentions.